Mejoramiento de camino vecinal cruce puente Quirihuac – Tres Cruces y Canseco del Distrito de Poroto – Provincia de TRUJILLO –LA LIBERTAD - Pretel Casanova, Edward Paúl (2016)
The people of District POROTO, aware of the problems that result to be cut off long ago, because the new road its original line was modified leaving the old road abandoned to date and due to growth in population centers urges the need for this approach to improve the old road corridor that has now become a road option for all people living around this way and likewise the villagers themselves bean and annexes used as alternate route due to lower travel time generating savings for the entire target population), for this reason they have resorted to the authorities of their jurisdiction to improve their road is made -. CROSSING BRIDGE QUIRIHUAC - SECTOR Canseco where it will connect with the existing track arriving poroto the district since this road it will be part of the road that will serve as an alternate road to communicate with the Province of Trujillo ie; Trujillo-Poroto, saving time using this route. It requires improving the improvement of 13,018 ml of road, place a layer of surfacing and asphalt with a platform 4 m of track with 50 cm side berms, with small squares crossing every 200 meters, works of art as sewers, passes irrigation channels. The work is estimated at a cost of TWO HUNDRED MILLION THREE HUNDRED EIGHTY THOUSAND FORTY-EIGHT 76/100 nuevos soles (S / 3, 280,548.76) This work promotes the District Municipality of Poroto, is funded by the region La Libertad. Backed by the authorities of all Caseríos Poroto with this work will benefit more than 3600 inhabitants of the district and towns that are located in the area of influence and would shift by this their agricultural production to Trujillo that is the great provincial market .